THE EFFECIENCY OF ENTERIC LACTOBACILLUS IN PREVENTING HEMORRHAGIC COLITIS AND BLOCKING SHIGA TOXINS PRODUCTIONS IN RATS MODELS INFECTED WITH ENTEROHEMORRHAGIC ESCHERICHIA COLI (EHEC) - Al wendawi, SH. A.; Al Rekaby, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The objective of this study was to investigate the prophylactic roles of human enteric derived Lactobacillus plantarum L1 (Ll) and Lactobacillus paracasei L2 (L2), on EHEC O157:H7 infection in rodent models (In vivo). The Lactobacillus suspensions (L1 and L2) were individually and orally administered to experimental rats at a daily two consecutives of 100 μl (108 CFU/ ml/rat) for up to two weeks. Thereafter, on the 8th day of experiment rats were orally challenged with one dose infection of EHEC (105 CFU/ml/rat). Animals mortality and illness symptoms have been monitored. There was no fatal EHEC infection in rats that had been pre‑colonized with the Lactobacillus strains, while most of EHEC infected rats were died (90%). The Stx1 and Stx2 levels were significantly lower (14 and 12 folds) in the L1and L2 pre-inoculated rates respectively, compared with those in the EHEC colonized group. Histological sections were proven the prophylactic roles of L1 and L2, whereas, no effective histological upsets were detected in Lactobacillus + EHEC- colonized rats. The cytopathic symptoms were predominant in kidney and intestinal sections of EHEC infected rats. The kidney sections cytopathy manifested to lining membrane ulceration, infiltration of mononuclear cells and glomerular and tubular epithelium necrosis. The striking attaching and effacing (A/E) lesions were prominent in intestinal sections of EHEC infected animal models.